2013
DOI: 10.14260/jemds/1386
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Operative Predictors of Difficult Laparoscopic Cholecystectomy; Comparisons of Two Scoring Systems. A Single Center Prospective Study”

Abstract: INTRODUCTION:Laparoscopic Cholecystectomy has evolved as the standard of care for the treatment of Gall Stone disease over the past decade. Several patient and procedure related factors have been implicated in setting of failure to complete the procedure by minimal invasive method and various scores have been developed to precisely predict a Difficult Laparoscopic Cholecystectomy. AIMS: The present study was conducted to ascertain various patient related preoperative risk factors for conversion of laparoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Vivek and colleagues traced difficulty as in creating pneumoperitoneum, accessing peritoneal cavity, releasing adhesions, identifying anatomy and extracting the gall bladder [13]. Previous attacks of acute cholecystitis, GB wall thickness, inability to delineate the anatomy and previous abdominal surgery are some of the factors that have been identified as potential risk factors for the conversion [14]. Accordingly in concordance with these studies [12][13][14] our data showed that burn cicatrization and supra-umbilical surgical scars led to difficult creation of pneumoperitoneum and difficult accessing peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vivek and colleagues traced difficulty as in creating pneumoperitoneum, accessing peritoneal cavity, releasing adhesions, identifying anatomy and extracting the gall bladder [13]. Previous attacks of acute cholecystitis, GB wall thickness, inability to delineate the anatomy and previous abdominal surgery are some of the factors that have been identified as potential risk factors for the conversion [14]. Accordingly in concordance with these studies [12][13][14] our data showed that burn cicatrization and supra-umbilical surgical scars led to difficult creation of pneumoperitoneum and difficult accessing peritoneal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Score of (0-5) indicates an easy approach while score of (6-10) indicates difficult approach and very difficult approach is observed with score of (11)(12)(13)(14)(15).…”
Section: Difficulty Scoringmentioning
confidence: 99%
“…Surge and coworkers offered a scoring system based on operative findings and the degree of cholecystitis in order to outline key operative findings [22]. Other authors were focused to establish predictive factors for difficult LC and conversion [23,24], or only for conversion [25], assuming that nowadays all cholecystectomies are treated laparoscopically. We tried to establish a simple model of prediction, which was then validated.…”
Section: Discussionmentioning
confidence: 99%